2016
DOI: 10.1155/2016/3290260
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Proteomics Identification of Serum Biomarkers of Two Chronic Hepatitis B Subtypes Diagnosed by Traditional Chinese Medicine

Abstract: Background. Chronic infection with hepatitis B virus (HBV) is a leading cause of cirrhosis and hepatocellular carcinoma. By traditional Chinese medicine (TCM) pattern classification, damp heat stasis in the middle-jiao (DHSM) and liver Qi stagnation and spleen deficiency (LSSD) are two most common subtypes of CHB. Results. In this study, we employed iTRAQ proteomics technology to identify potential serum protein biomarkers in 30 LSSD-CHB and 30 DHSM-CHB patients. Of the total 842 detected proteins, 273 and 345… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…KEGG pathway annotation 29 revealed that the DEPs in AHT and YDSK group both mainly functioned in the signaling pathways of systemic lupus erythematosus (hsa05322), staphylococcus aureus infection (hsa05150), tuberculosis (hsa05152), viral myocarditis (hsa05416), PI3K-Akt signaling pathway (hsa04151) and phospholipase D signaling pathway (hsa04072) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KEGG pathway annotation 29 revealed that the DEPs in AHT and YDSK group both mainly functioned in the signaling pathways of systemic lupus erythematosus (hsa05322), staphylococcus aureus infection (hsa05150), tuberculosis (hsa05152), viral myocarditis (hsa05416), PI3K-Akt signaling pathway (hsa04151) and phospholipase D signaling pathway (hsa04072) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A flurry of applications, e.g . detection of diagnosis biomarkers for pulmonary tuberculosis 28 , chronic hepatitis B 29 and prenatal neural tube defects 30 , have been driven in past decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fibulin‐5 was identified as a novel protein expressed in relation to hepatic fibrosis . The differential expression of microfibril‐associated glycoprotein 4, lumican, and collagen alpha‐1 chain in association with hepatic fibrosis was confirmed by Yang et al . Hemopexin and signal‐induced proliferation‐associated 1 like 1 were proved to be potential serum markers of CCl 4 ‐induced liver fibrogenesis among analyzed proteins by Marfa et al.…”
Section: Introductionmentioning
confidence: 93%
“…In terms of viral infections, Dengue fever, Hepatitis B and C, HIV and Simian immunodeficiency virus (SIV) have been studied using iTRAQ of plasma and serum samples. Liu et al compared plasma from individuals with chronic hepatitis B virus‐associated hepatocellular carcinoma (HCC), non‐malignant cirrhosis, chronic hepatitis B, and healthy individuals.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%